A Distributed Algorithm for Distribution Network Reconfiguration - Gao, Yuanqi; Wang, Peng; Yu, Nanpeng (2018 China International Conference on Electricity Distribution (CICED), 2018)
Distribution network reconfiguration algorithms change the status of sectionalizing and tie switches to reduce network line losses, relieve network overloads, minimize loss of load, or increase hosting capacity for distributed energy resources. Most of the existing work adopt centralized or hierarchical approaches to solve the network reconfiguration problem. This paper proposes a distributed scheme for network reconfiguration. In the distributed approach, the switches are represented by edge computing agents who communicate and work collectively with their neighbors to find the optimal reconfiguration solution. This scheme breaks the complex computation tasks required by centralized algorithms into much smaller ones. It also relieves the communication and data sharing burden via neighbor-to-neighbor communication. Simulation results on a 16-bus distribution test feeder demonstrate that the quality of the distributed solution is comparable to that of the centralized approach.